2008
DOI: 10.1007/s10620-008-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Randomized and Controlled Treatment Trials for Achalasia

Abstract: Pharmacological therapy, botulinum toxin injection, pneumatic dilatation, and surgical myotomy are the primary therapeutic modalities for achalasia, for which laparoscopic myotomy is recommended as state-of-the-art therapy. However, its efficacy and safety remain unclear compared with other approaches in the treatment of achalasia. We searched electronic databases (MEDLINE, EMBASE, Cochrane Central Registry of Controlled Trials, LILACS-Latin American, Caribbean health science literature, and Science Citation I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(44 citation statements)
references
References 37 publications
2
37
1
4
Order By: Relevance
“…showed an association between larger volume of surgery and improved perioperative outcome [14] due to a steep learning curve for LHM [4], [7], [8]. Long–term efficacy of LHM is reported to range between 88% and 95% [6], [15], [16], [17], [18], [19]. PD, when applied in a graded fashion, has been shown to be non-inferior in efficacy to LHM in the short term [15], [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed an association between larger volume of surgery and improved perioperative outcome [14] due to a steep learning curve for LHM [4], [7], [8]. Long–term efficacy of LHM is reported to range between 88% and 95% [6], [15], [16], [17], [18], [19]. PD, when applied in a graded fashion, has been shown to be non-inferior in efficacy to LHM in the short term [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Long–term efficacy of LHM is reported to range between 88% and 95% [6], [15], [16], [17], [18], [19]. PD, when applied in a graded fashion, has been shown to be non-inferior in efficacy to LHM in the short term [15], [16]. A recent meta-analysis suggests that long-term results however are in favour of surgery [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review of six randomized controlled trials including 178 patients evaluated symptom recurrence after esophageal dilation versus endoscopic botulinum toxin A injection at one, six, and 12 months after treatment. Thirty percent of patients undergoing dilation experienced symptom recurrence and treatment failure at 12 months versus 74% of patients who received botulinum toxin A 42. Furthermore, a systematic review and meta-analysis of 105 papers that reported on 761 patients with achalasia who underwent endoscopic treatment with esophageal dilation or botulinum toxin A showed that symptom relief was better for dilation, and the necessity for further treatment was significantly reduced 43…”
Section: Endoscopic Therapiesmentioning
confidence: 99%
“…showed that there were significant differences in remission rate (laparoscopic myotomy 95.0% vs. pneumatic dilation 77.8%, P = 0.001) and relapse rate (laparoscopic myotomy 5.1% vs. pneumatic dilation 35.71%, P = 0.007), indicating that laparoscopic myotomy offered better clinical result than pneumatic dilation. [13] However, this meta-analysis had been challenged by a large and more recent randomized prospective trial, where Boeckxstaens et al . showed that after 2 years of follow-up, LHM, as compared with PD, was not associated with superior rates of therapeutic success.…”
Section: Discussionmentioning
confidence: 99%